Policy actions for building resilience of fisheries development in a changing climate - Ministry of Agriculture, Livestock, Fisheries and Cooperatives, Kenya (2020)
The fisheries sub-sector in Kenya plays an important role in the national economy. It is an important source of food, nutritional security, employment and foreign exchange. The fisheries and aquaculture sector in Kenya contributes about 0.8% of the country’s gross domestic product (GDP). It is estimated that the sector employs 500,000 people directly, and supports about two million people indirectly, working as fishers, traders, processors, suppliers and merchants of fishing accessories and their dependents.